2021
DOI: 10.1186/s12933-021-01268-9
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride–glucose index and the incidence of atherosclerotic cardiovascular diseases: a meta-analysis of cohort studies

Abstract: Background Insulin resistance has been demonstrated to be involved in the pathogenesis of atherosclerotic cardiovascular diseases (ASCVDs). This study evaluated the association between the triglyceride–glucose (TyG) index, a novel surrogate indicator of insulin resistance, and the incidence of ASCVDs in people without ASCVDs at baseline by performing a meta-analysis. Methods Cohort studies reporting the multivariate-adjusted association between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
165
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 37 publications
5
165
3
2
Order By: Relevance
“…The accuracy of TyG index in the diagnosis of insulin resistance was consistent with that of HIEC and HOMA-IR (4). A recent meta-analysis involving 5,731,294 participants reported that a higher TyG index might be independently associated with a higher incidence of atherosclerotic cardiovascular diseases (ASCVDs), CAD, and stroke in people without ASCVDs at baseline (24). To the best of our knowledge, this study is the first study to evaluate the relationship between the TyG index and adverse outcomes within the population of hypertensive patients without diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…The accuracy of TyG index in the diagnosis of insulin resistance was consistent with that of HIEC and HOMA-IR (4). A recent meta-analysis involving 5,731,294 participants reported that a higher TyG index might be independently associated with a higher incidence of atherosclerotic cardiovascular diseases (ASCVDs), CAD, and stroke in people without ASCVDs at baseline (24). To the best of our knowledge, this study is the first study to evaluate the relationship between the TyG index and adverse outcomes within the population of hypertensive patients without diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, we compared the diagnostic values of the TyG index, FBG, and TG for arterial stiffness by receiver operating characteristics curve and the area under the curve, and found that TyG index had a better predictive value than FBG and TG alone (data not shown), which was consistent with previous studies [ 39 – 41 ]. With an increasing number of studies supporting the strong predictive value of TyG index for the development of CVDs and other chronic diseases such as type 2 diabetes [ 42 , 43 ], TyG index has been widely recognized as a simple and effective marker for disease prediction and prevention. A high TyG index could alert people to establish early lifestyle changes able to reduce the progression or incidence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…As for the risk of stroke associated with elevated TyG index, an earlier meta-analysis showed that a higher TyG index was associated with a 26% increased risk of stroke among participants without atherosclerotic cardiovascular diseases at baseline ( 52 ). Similarly, in a cross-sectional study with a general population, the incidence of ischemic stroke increased by 22.8% for each additional SD in the TyG index ( 53 ).…”
Section: Discussionmentioning
confidence: 99%